New and improved varieties for everyone? Gendered patterns of wheat varietal turnover among social groups in the Indian state of Bihar - Herforth, Nico; Gartaula, Hom Nath (Informa UK Limited, 2025)
For smallholder farmers in the Global South, rapid varietal turnover is an important means of coping with the risks arising from the spread of pests or diseases and for increasing crop yields. Varietal turnover in wheat systems in many states of India, however, is inadequately slow. At the same time, the Indian wheat sector is characterized by deep-rooted social inequalities, pronounced by the social differentiation of wheat farmers, such as gender, caste or ethnicity, wealth, and their intersectionalities. This article asks whether these social groups are excluded from the adoption of new and improved wheat varieties. The study builds on household survey data collected from 759 wheat farmers in Bihar, one of the poorest states in India. Our findings demonstrate only small differences of varietal turnover across heterogeneous social groups of farmers. In particular, we find only small differences in varietal turnover between female-headed and male-headed households (albeit their already low levels of varietal turnover) and their intersecting social identities. However, marginalized caste farmers appear to be more disadvantaged, as they tend to cultivate older wheat varieties, which deserves closer attention from policymakers. We discuss important directions for future research on the gendered analysis of wheat-based cropping systems.